Risk factors of perioperative blood transfusion in elderly patients with femoral intertrochanteric fracture. Issue 15 (April 2020) - Dai, Cheng-Qian; Wang, Li-Hong; Zhu, Ye-Qin; Xu, Guo-Hong; Shan, Jun-Biao; Huang, Wei-Chun; Wei, Li-Hong; Zhou, Fang-Lun; Li, Yong
Abstract : Abstract: This study aimed to discuss the risk factors of perioperative blood transfusion after the application of proximal femoral nail antirotation (PFNA) in the treatment of elderly patients with femoral intertrochanteric fracture (FIF). Moreover, this study also aimed to analyze the causes of perioperative blood transfusion and provide guidance for clinical treatment. Records of elderly patients with FIF who were treated with PFNA in our hospital from September 2014 to May 2017 were reviewed. They were divided into transfused and nontransfused groups. The Student t test, Chi-squared test, and Fisher exact test were used in univariate analysis of 11 variables. Multivariate logistic regression analysis was performed to analyze the possible risk factors associated with postoperative blood transfusion after the application of PFNA in elderly patients with FIF. Correlations were sought using the Spearman rank correlation analysis. The univariate analysis showed that age, sex, type of fracture, admission hemoglobin (Hb), admission albumin, and intraoperative blood loss were significantly associated with perioperative blood transfusion ( P = .000, .019, .000, .000, .000, and .007, respectively). The multivariate logistic regression analysis demonstrated that age ( P = .019, odds ratio [OR] = 1.062), type of fracture ( P = .001, OR = 4.486), and admission Hb ( P = .000, OR = 0.883) were independent risk factors of postoperative blood transfusion. We found a significant positive correlation between perioperative blood transfusion and age ( r = 0.264, P = .000) and type of fracture ( r = 0.409, P = .000), but a negative correlation between perioperative blood transfusion and admission Hb ( r = −0.641, P = .000). The main factors affecting perioperative blood transfusion are age, fracture type, and admission Hb. These results indicate that, in high-risk patients who are older in age, more unstable fractures, and lower admission Hb, monitoring Hb concentrations during the perioperative period is important to correct severe anemia in a timely manner and avoid exacerbating existing underlying diseases and inducing severe complications.